Hezbollah's Military Intervention in Syria: political choice or religious obligation? - Tokmajyan, Armenak (Approaching religion, 2014)
Hezbollah has been an important political and military actor in Lebanon and the Middle East since the mid-1980s. Its popularity grew especially after successfully deterring the Israeli invasion of Lebanon in 2006. With the emergence of the so-called Arab Spring, however, the party’s popularity declined for many reasons. One of these was its military intervention in Syria on the side of the Syrian government. This event has been interpreted in various ways, sometimes explaining it as religiously-motivated decision, due to Hezbollah’s strong affiliation to Shia Islam. This empirical research finds that, on the contrary, Hezbollah’s intervention is politically rather than religiously motivated. The data presented here shows that Hezbollah politicizes certain aspects of the religious sensitivities in the region in order to mobilize troops, yet, a study of its military activities inside Syria indicates that Hezbollah actually follows its political and geostrategic interests.